RESPONSIBILITY AND PROCEDURE FOR DISSOLUTION OF PT BY GMS: A COMPARISON OF INDONESIAN AND MALAYSIAN LAW - Salsabila Paramadani (Realism: Law Review, 2023)
The purpose of this research is to examine how the legal framework in Indonesia regulates the dissolution of companies, particularly when it has been approved by shareholders in a General Meeting of Shareholders (GMS). This study also aims to conduct a comparison with the company dissolution mechanism in Malaysia. The method used is a literature review, which involves examining laws and regulations as well as analyzing relevant legal concepts. The findings indicate that there are similarities and differences between the legal systems of the two countries. These differences stem from the distinct legal traditions each country follows: Indonesia adopts a civil law system, while Malaysia follows a common law system. Consequently, the approaches and regulatory styles in each country differ,